2017
DOI: 10.1016/j.foodchem.2017.02.086
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic interaction chromatography and evaporative light scattering detection for the determination of polar analytes in Belgian endive

Abstract: Belgian endive (Cichorium intybus L. var. foliosum Hegi), a popular produce in northern Europe, has been thoroughly studied in regard to its bitter sesquiterpene lactones content. Much less is known about on its sweetness and crunchiness, which are typically linked to the content of polar compounds such as sugars, organic acids and salts. Through HILIC-HPLC-MS, it was shown that simple sugars, amino acids, and potassium chloride are abundant in Belgian endive extracts. Subsequently, a HILIC-HPLC-ELSD method fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The authors compared HPLC on a strong anion-exchange column where isomaltulose was separated from glucose, fructose, and trehalulose in 11 min. In 2017 Annaratone et al [ 52 ] reported a six-minute analysis (on a 10 cm column) of polar analytes in Belgian endive by HILIC HPLC-ELSD, where isomaltulose served as an internal standard.…”
Section: Introductionmentioning
confidence: 99%
“…The authors compared HPLC on a strong anion-exchange column where isomaltulose was separated from glucose, fructose, and trehalulose in 11 min. In 2017 Annaratone et al [ 52 ] reported a six-minute analysis (on a 10 cm column) of polar analytes in Belgian endive by HILIC HPLC-ELSD, where isomaltulose served as an internal standard.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, compared with normal‐phase chromatography, the mobile phase of HILIC is compatible with mass spectrometry (MS) (especially electrospray ionization mass spectrometry), and thus, it improves the detection sensitivity . Thus, HILIC has been widely applied in various fields, including pharmaceutical analysis, food analysis, biomedical science, analytical chemistry, etc. In addition, many new stationary phases have been developed by introducing a variety of functional groups like hydrophilic macromolecules and ionic liquids, which can provide wider ranges of applications for HILIC …”
Section: Introductionmentioning
confidence: 99%